2006
DOI: 10.1261/rna.100806
|View full text |Cite
|
Sign up to set email alerts
|

A previously unidentified activity of yeast and mouse RNA:pseudouridine synthases 1 (Pus1p) on tRNAs

Abstract: Mouse pseudouridine synthase 1 (mPus1p) was the first vertebrate RNA:pseudouridine synthase that was cloned and characterized biochemically. The mPus1p was previously found to catalyze C formation at positions 27, 28, 34, and 36 in in vitro produced yeast and human tRNAs. On the other hand, the homologous Saccharomyces cerevisiae scPus1p protein was shown to modify seven uridine residues in tRNAs (26, 27, 28, 34, 36, 65, and 67) and U44 in U2 snRNA. In this work, we expressed mPus1p in yeast cells lacking scP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 57 publications
(79 reference statements)
5
55
0
Order By: Relevance
“…The recent development of RNA bisulfite sequencing (Schaefer et al 2009), and the use of methods for the purification and site-specific methylation analysis of defined tRNAs (Hengesbach et al 2008) allowed us to identify additional tRNAs that were methylated by Dnmt2 in Drosophila, thus providing evidence for multisubstrate methyltransferase activity of Dnmt2. Multisubstrate specificity has been described for other RNA modification enzymes, including pseudouridine synthase 1 (Behm-Ansmant et al 2006), and, significantly, TRM4, the only other characterized cytosine-5 tRNA methyltransferase (Motorin and Grosjean 1999). Considering that TRM4 methylates minisubstrates as small as 40 nucleotides, it remains a possibility that other unidentified substrate RNAs (e.g., small regulatory RNAs) might be methylated by RNA methyltransferases such as Dnmt2.…”
Section: Functional Characterization Of Dnmt2mentioning
confidence: 99%
“…The recent development of RNA bisulfite sequencing (Schaefer et al 2009), and the use of methods for the purification and site-specific methylation analysis of defined tRNAs (Hengesbach et al 2008) allowed us to identify additional tRNAs that were methylated by Dnmt2 in Drosophila, thus providing evidence for multisubstrate methyltransferase activity of Dnmt2. Multisubstrate specificity has been described for other RNA modification enzymes, including pseudouridine synthase 1 (Behm-Ansmant et al 2006), and, significantly, TRM4, the only other characterized cytosine-5 tRNA methyltransferase (Motorin and Grosjean 1999). Considering that TRM4 methylates minisubstrates as small as 40 nucleotides, it remains a possibility that other unidentified substrate RNAs (e.g., small regulatory RNAs) might be methylated by RNA methyltransferases such as Dnmt2.…”
Section: Functional Characterization Of Dnmt2mentioning
confidence: 99%
“…Another interpretation is that a separate pseudouridine synthase exists for position 44 and that its activity is influenced by the presence or absence of pugU2-35/45. Such a synthase (Pus1p) has been identified in yeast (Massenet et al 1999), and its orthologs are presumably responsible for the corresponding modification in higher eukaryotes (Behm-Ansmant et al 2006).…”
Section: Probing New Scarnas For Guide Rna Activitymentioning
confidence: 99%
“…To this end, the tRNA:C72-synthase activity of cell-free extracts prepared from different strains was tested on a transcript of the mitochondrial tRNA Met i(CAU) labeled by [a-32 P]ATP incorporation. As evidenced by thin layer chromatography (TLC) analysis of the labeled RNAse T2 digestion products, none of the gene disruptions affected the activity of the extracts (Table 1, see also Behm- Ansmant et al 2006). Thus, Pus1p and Pus2p are probably not involved in C formation at position 72.…”
Section: Resultsmentioning
confidence: 99%
“…We found that two distinct enzymes, Rib2p/Pus8p and Pus9p, are required for C32 formation in tRNAs, depending on their cytoplasmic or mitochondrial localization, and cytoplasmic Rib2p/Pus8p contains both a tRNA:C32-synthase domain and a DRAP-deaminase domain (Behm- Ansmant et al 2004). Pus1p is an RNA:C-synthase with a multisite specificity (tRNA positions 1, 26, 27, 28, 34, 36, 65, and 67) Behm-Ansmant et al 2006). In addition, it also modifies U2 snRNA at position 44 (Massenet et al 1999).…”
Section: Introductionmentioning
confidence: 99%